Sensorless control of PMSM drive for electric vehicle applications - Chouireb Saad; Bendjedia Bachir (Université Amar Thelidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Génie Mechanique, 2022)
This these focuses on improving the reliability of a traction chain for electric vehicle applications, If there is a failure in the speed sensor In fact, there are already existing sensors in the traction chains however, they generate significant additional costs due to their frequent failure and the need for replacement. Thus, speed sensorless control of the AC drive systems allows the elimination of the sensors of the machine and therefore to avoid their cost, the objective of the thesis is to develop new methods that accompany the motors control to ensure better performance of the traction chain in the absence or failure of the speed sensor In this thesis, the observers is presented by model reference adaptive system method (MRAS), the sliding mode observer (SMO) and the extended Kalman filter (EKF) to be used in the control of the conversion chain The three methods were used with vector control of the traction chain in two cases. The first is the absence of the speed sensor in a normal condition. The second is when the failure happen at the speed sensor, which is replaced by one of the three observers systems to ensure the continuity of drive operation and thus improve the performance of the traction chain of the electric vehicle
OPTION: ELECTROMECHANICS